Distribution of Nanoparticle Number Concentrations at a Nano-TiO2 Plant - Yang, Yi; Mao, Ping; Wang, Zheng-Ping; Zhang, Jin-Hua (Aerosol and air quality research, 2012)
Nanoparticle number concentration distributions were measured at various sites in a plant manufacturing nano-sized titanium dioxide powder. It was found that aerosol nanoparticles suspended in the air were mainly in the form of agglomerated particles, and had the average diameters of 124.2 nm and 524.4 nm, respectively. The number concentration of aerosol particles increased with source height, but decreased with distance from the source. The concentration was highly affected by the dispersive forces of the discharging port, and the suspension and the agglomeration of particles. The aerosol particles accumulated after a long working time, and the concentration was reduced at large suspending distances. In contrast, the concentration of primary particles was higher for a working time of less than 2 hours, and returned to normal levels after 3 hours, due to the accumulation and agglomeration effects experienced by the primary particles. Motivated by these findings, an aerosol enclosure was developed in this study, and it showed excellent control over the distribution of aerosol particles, including the agglomerated and primary particles. This is thus a promising approach to achieve effective and efficient personal protection in the workspace.